1990
DOI: 10.1002/macp.1990.021910401
|View full text |Cite
|
Sign up to set email alerts
|

In vivo characteristics of low‐molecular‐weight copoly(L‐lactic acid/DL‐hydroxyisocaproic acid) with parabolic‐type and S‐type degradation pattersn

Abstract: An amorphous copolyester of c l a g c acid (LA) and Dbhydroxyisocaproic acid (HICA) with a number-average molecular weight (MJ of 1 600-4800 was synthesized by direct copolycondensation in the absence of catalysts, in order to develop a biodegradable carrier for drug delivery systems. The in vivo degradation pattern was changed into an S-type from a parabolic-type with an increase in molecular weight of copolyester. A luteinizing hormone-releasing hormone agonist, ~~S -G~~'~-[ D -L~U~-L H -R H ethylamide, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 10 publications
3
14
0
Order By: Relevance
“…In any case, the exponential decrease of the average molecular weight with apparent first-order degradation (without the appearance of bimodality) indicated a random chain scission and a negligible effect of autocatalysis. Similar studies on the effect of composition on degradation had also been reported by Wang and Wu [5]. In a study [5] recorded.…”
Section: Degradationmechanismssupporting
confidence: 81%
See 4 more Smart Citations
“…In any case, the exponential decrease of the average molecular weight with apparent first-order degradation (without the appearance of bimodality) indicated a random chain scission and a negligible effect of autocatalysis. Similar studies on the effect of composition on degradation had also been reported by Wang and Wu [5]. In a study [5] recorded.…”
Section: Degradationmechanismssupporting
confidence: 81%
“…Similar studies on the effect of composition on degradation had also been reported by Wang and Wu [5]. In a study [5] recorded. It might be noted that it was quite difficult to measure the percent water uptake for samples after the day.…”
Section: Degradationmechanismssupporting
confidence: 81%
See 3 more Smart Citations